Diverse unfreedoms
1 online resource (1 volume)
Keywords: "The legacies of plantation slavery continue to inhabit, animate, and haunt the diverse forms of unfreedom that mark our present. Diverse Unfreedoms charts a new way of thinking through these legacies of unfreedom via a more entangled and multidirectional model of what makes for historical change and continuity in practices and relationships of subjugation. This volume troubles the stark opposition between slavery and freedom by foregrounding the diversity of types of exploitation above and beyond the most extreme forms of dehumanization characterized by slavery. The chapters, from multiple disciplines and discussing diverse regions and historical periods, illustrate the significance of interdisciplinary and international perspectives in understanding diverse unfreedoms, and offer a nuanced account of historical change and continuity in systems that generate and perpetuate unfreedom. Through examining the frictions that mark certain key moments of legal, social, and institutional transition, the essays in this volume express the limits of liberal humanist projects and present a critique of the liberal notion of freedom as the necessary horizon of emancipatory imagination and labor"--